Probiotics-Containing Mucoadhesive Gel for Targeting the Dysbiosis Associated with Periodontal Diseases. (27th February 2022) - Giannini, Giuseppe; Ragusa, Irene; Nardone, Giulia Nerina; Soldi, Sara; Elli, Marina; Valenti, Piera; Rosa, Luigi; Marra, Emanuele; Stoppoloni, Daniela; Merlo Pich, Emilio
Abstract : Objective . Periodontitis is a common disorder that leads to the loss of both tooth and personal well-being, contributing to worsen the risk for metabolic and cardiovascular diseases. Recently, probiotics, characterized by rapid oral dispersion, have been topically used. Here, we present data of a mucoadhesive gel containing probiotics, capable of ensuring a slow release of bacteria to prevent and treat periodontitis. Methods . An original mucoadhesive gel (AL0005) that is anhydrous and of food grade, loaded with the blend of lactobacilli and plants' dry extracts, has been assayed. Results . The release kinetics of the bacterial mixture in different experimental models in vitro, including simulated saliva or physiological solutions, showed a significant and stable release for 5–8 hours. In one in vivo study of a mouse model of periodontitis, a locally applied mucoadhesive gel enriched with probiotic strains improved significantly the tissue pathology when compared with vehicle-exposed mice. Conclusions . Together, the results suggest that this mucoadhesive gel can be useful in the normalization of the gum bacterial flora and improvement of the tissue pathology of gum disorders.